A Product-Based Approach to Translation Training - Al-Mijrab, Ramadan (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThis study seeks to demonstrate that active interaction between learner and teacher rather than passive reception by the teacher - as obtains in traditional teaching models - is essential. A product-based analysis of actual training makes it possible to identify a translation problem and subsequently apply theoretical considerations. Depending on the nature of the text being translated, error analysis can be used effectively not only for monitoring student progress but also for appraising general performance.